Partial Revelation of Information in Experimental Asset Markets - Copeland, Thomas E.; Friedman, Daniel (Journal of Finance, 1991)
We develop a model of market efficiency assuming private information is partially revealed to uninformed traders via the behavior of those who are informed. This partial revelation of information (PRE) model is tested in fourteen computerized double auction laboratory markets. It explains the market value and allocation of purchased information, and asset allocations, better than either a fully revealing information model (FRE strong-form efficiency) or a nonrevealing expectations model; but it takes second place to FRE in explaining asset prices. We conjecture that refined versions of PRE may provide insight into “technical analysis” and minibubbles in securities markets.